Upliftment Through The Family Hope Program (PKH) In Sei Rampah District, Serdang Bedagai Regency - Mukti Pradani, Bayu; Erlina, Erlina; Sirojuzilam, Sirojuzilam (International Journal of Science, Technology & Management, 2023)
The aim of this research is to analyze the impact of the Family Hope Program (PKH) social assistance on the welfare of the population in Sei Rampah District, Serdang Bedagai Regency; to examine the influence of PKH mentoring on the welfare of the population in Sei Rampah District, Serdang Bedagai Regency; to assess the impact of PKH facility services on the welfare of the population in Sei Rampah District, Serdang Bedagai Regency; and to investigate the influence of complementary assistance programs within PKH on the welfare of the population in Sei Rampah District, Serdang Bedagai Regency. The quantitative analysis method was employed, utilizing multiple regression analysis to address the first, second, third, and fourth research problem formulations. The hypothesis testing involved R2, F-test, and t-test. The findings of this study are as follows: 1) The social assistance variable has a positive and significant impact on the welfare of the population in Sei Rampah District, Serdang Bedagai Regency; 2) The mentoring variable has a positive and significant impact on the welfare of the population in Sei Rampah District, Serdang Bedagai Regency; 3) The facility services variable has a positive and significant impact on the welfare of the population in Sei Rampah District, Serdang Bedagai Regency; and 4) The complementary assistance variable has a positive and significant impact on the welfare of the population in Sei Rampah District, Serdang Bedagai Regency.